Age-dependent astroglial vulnerability to hypoxia and glutamate: the role for erythropoietin. - Ali Lourhmati; Gayane H Buniatian; Christina Paul; Stephan Verleysdonk; Reinhild Buecheler; Marine Buadze; Barbara Proksch; Matthias Schwab; Christoph H Gleiter; Lusine Danielyan (PLoS ONE, 2013)
Extracellular accumulation of toxic concentrations of glutamate (Glu) is a hallmark of many neurodegenerative diseases, often accompanied by hypoxia and impaired metabolism of this neuromediator. To address the question whether the multifunctional neuroprotective action of erythropoietin (EPO) extends to the regulation of extracellular Glu-level and is age-related, young and culture-aged rat astroglial primary cells (APC) were simultaneously treated with 1mM Glu and/or human recombinant EPO under normoxic and hypoxic conditions (NC and HC). EPO increased the Glu uptake by astrocytes under both NC and especially upon HC in culture-aged APC (by 60%). Moreover, treatment with EPO up-regulated the activity of glutamine synthetase (GS), the expression of glutamate-aspartate transporter (GLAST) and the level of EPO mRNA. EPO alleviated the Glu- and hypoxia-induced LDH release from astrocytes. These protective EPO effects were concentration-dependent and they were strongly intensified with age in culture. More than a 4-fold increase in apoptosis and a 2-fold decrease in GS enzyme activity was observed in APC transfected with EPO receptor (EPOR)-siRNA. Our in vivo data show decreased expression of EPO and a strong increase of EPOR in brain homogenates of APP/PS1 mice and their wild type controls during aging. Comparison of APP/PS1 and age-matched WT control mice revealed a stronger expression of EPOR but a weaker one of EPO in the Alzheimer's disease (AD) model mice. Here we show for the first time the direct correlation between the extent of differentiation (age) of astrocytes and the efficacy of EPO in balancing extracellular glutamate clearance and metabolism in an in-vitro model of hypoxia and Glu-induced astroglial injury. The clinical relevance of EPO and EPOR as markers of brain cells vulnerability during aging and neurodegeneration is evidenced by remarkable changes in their expression levels in a transgenic model of AD and their WT controls.